2002
DOI: 10.1136/jnnp.73.5.508
|View full text |Cite
|
Sign up to set email alerts
|

Relation between medial temporal atrophy and functional brain activity during memory processing in Alzheimer's disease: a combined MRI and SPECT study

Abstract: Objective: To investigate the relation between atrophy of the hippocampal region and brain functional patterns during episodic memory processing in Alzheimer's disease. Patients and methods: Whole brain structural magnetic resonance imaging (MRI) data and single photon emission computed tomography (SPECT) measures of regional cerebral blood flow (rCBF) were obtained during a verbal recognition memory task in nine subjects with mild Alzheimer's disease and 10 elderly healthy controls. Using the statistical para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
30
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 54 publications
12
30
0
3
Order By: Relevance
“…Our study also supports functional connectivity studies proposing a functional relationship between the hippocampus and the posterior cingulate gyrus. In agreement, Garrido et al [27] observed a correlation of hippocampal grey matter density with memory-related activation in the left posterior cingulate gyrus in subjects with AD. Chetelat et al [9] reported that reductions in retrieval performance correlated with hippocampal atrophy but also with reduced resting metabolism in the posterior cingulate gyrus, indicating a morphological and functional dissociation.…”
Section: Discussionsupporting
confidence: 67%
“…Our study also supports functional connectivity studies proposing a functional relationship between the hippocampus and the posterior cingulate gyrus. In agreement, Garrido et al [27] observed a correlation of hippocampal grey matter density with memory-related activation in the left posterior cingulate gyrus in subjects with AD. Chetelat et al [9] reported that reductions in retrieval performance correlated with hippocampal atrophy but also with reduced resting metabolism in the posterior cingulate gyrus, indicating a morphological and functional dissociation.…”
Section: Discussionsupporting
confidence: 67%
“…No campo dos estudos de neuroimagem funcional, diversos estudos utilizando PET ou SPECT têm demonstrado padrão típico de hipofuncionamento cortical de repouso em pacientes portadores de DA, afetando particularmente áreas temporais e parietais (Matsuda et al, 2002;Garrido et al, 2002). Este padrão de hipometabolismo está diretamente relacionado à intensidade dos déficits de memória e atenção nestes pacientes (Matsuda et al, 2002), e difere dos sinais de hipoatividade multi-focais, de localização variada, que podem surgir em quadros de DMI (Yoshikawa et al, 2003).…”
Section: Neuroimagem E Demênciasunclassified
“…Many scientific studies involving this age group typically have a greater number of female participants, 18 possibly because i) women have a longer life expectancy (6 years longer on average), ii) women have a higher level of social support, are more likely to seek new sources of support, have a greater ability to form bonds, enjoy affectionate relations, and assemble in a group, and iii) women have lower biological vulnerability, as the rate of lethal diseases is higher among men. 66 This review shows some variability among the studies regarding how PA is measured. Only three studies 31,37,47 used direct measures to assess PA.…”
Section: Characteristics Of the Studymentioning
confidence: 99%